1997
DOI: 10.1172/jci119799
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic secretion of phospholipid vesicles in the mouse critically depends on mdr2 or MDR3 P-glycoprotein expression. Visualization by electron microscopy.

Abstract: Hepatocellular secretion of bile salts into the biliary space induces phospholipid and cholesterol secretion, but the mechanism for integrated lipid secretion is poorly understood. Knockout mice unable to make the canalicular membrane mdr2 P-glycoprotein exhibit normal rates of bile salt secretion, yet are virtually incapable of secreting biliary phospholipid and cholesterol. As the mdr2 P-glycoprotein is thought to mediate transmembrane movement of phospholipid molecules, this mouse model was used to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
80
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(86 citation statements)
references
References 33 publications
4
80
0
Order By: Relevance
“…44 The vesicular structures observed in canaliculi of mutant livers are likely formed as a consequence of the elevated biliary cholesterol levels. These structures must not be confused with the vesicles that have been described by Crawford and coworkers 45 to support the vesiculation theory, a proposed mechanism for biliary phospholipid excretion. In contrast to the vesicles observed in our study, they described unilamellar vesicles, most of which were adherent to the canalicular membrane.…”
Section: Discussionsupporting
confidence: 68%
“…44 The vesicular structures observed in canaliculi of mutant livers are likely formed as a consequence of the elevated biliary cholesterol levels. These structures must not be confused with the vesicles that have been described by Crawford and coworkers 45 to support the vesiculation theory, a proposed mechanism for biliary phospholipid excretion. In contrast to the vesicles observed in our study, they described unilamellar vesicles, most of which were adherent to the canalicular membrane.…”
Section: Discussionsupporting
confidence: 68%
“…A relevant loss of Bsep into the bile canalicular lumen during administration of TLCA appears unlikely to explain the decrease of Bsep density in canalicular membranes. Although hydrophobic bile salts have been shown to induce external hemileaflet exocytosis of phospholipid vesicles, 38,39 the mechanisms for protein retention within the canalicular membrane during biliary phospholipid secretion appear to be very effective. 40 Thus, Bsep retrieval into the pericanalicular zone (see Figures 1 and 2) appears to be the predominant mechanism leading to Bsep deprivation of apical hepatocyte membranes exposed to TLCA.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been presented that Abcb4 (Mdr2), which rate limits biliary phosphatidylcholine secretion at the canalicular membrane, may function as a specific flippase for phosphatidylcholines, thereby providing a selective mechanism for phosphatidylcholines (36). Because of the high rates of Abcb4-mediated biliary phosphatidylcholine secretion (37,38), hepatocytes would be expected to possess efficient mechanisms to replenish the canalicular membrane as phosphatidylcholine molecules are removed during bile formation. Earlier observations that microtubule-disrupting agents could inhibit biliary secretion of cholesterol and phospholipid (39)(40)(41) suggested that transport of vesicles along microtubules could provide a resupply route (reviewed in 37).…”
Section: Discussionmentioning
confidence: 99%